Delicate dining with a date and burger binging with buddies: impression management across social settings and consumers’ preferences for masculine or feminine foods - Gasiorowska, Agata; Folwarczny, Michał; Tan, Lynn K. L.; Otterbring, Tobias (Frontiers in Nutrition, 2023)
Consumers often use their food choices as an impression management strategy to signal desirable aspects about themselves to others, especially in public places like restaurants and cafeterias, where the presence of others can promote certain consumption choices and preference patterns. In mating contexts, people prefer gender-typical traits and characteristics in a potential partner. Food options can also be classified according to their gender typicality, with certain alternatives perceived as feminine (e.g., salad, seafood) and with other options perceived as more masculine (e.g., steak, burger). Drawing on impression management theories from the drinking and dining domain and literature on sex differences in human mate preferences, we present a high-powered experiment investigating whether consumers’ preferences for masculine or feminine foods depend on the social setting in which the food consumption takes place: dining with an attractive date (mating) or meeting and eating with friends (non-mating). Participants (N = 162, 46.9% females, 53.1% males; age M = 41.8 years, SD = 14.5) were randomly assigned to one of the two experimental conditions (mating vs. non-mating) and were asked to indicate their food preferences for 15 dishes that differed markedly in perceived femininity/masculinity. Consistent with our theorizing, females (males) generally had a stronger preference for foods perceived as more feminine (masculine), thereby supporting the gender-typicality thesis at the aggregate level. Furthermore, females in the mating condition—but not females in the non-mating condition—reported significantly stronger preferences for more feminine food alternatives. However, in direct contrast to our theorizing, males preferred more masculine meals in the non-mating condition (i.e., when dining with friends), whereas this gender-typical tendency did not emerge in the mating condition (i.e., when dining with an attractive date). We discuss the theoretical and practical implications of these findings and present a set of fruitful avenues for future research.